Do Weak Institutions Prolong Crises? On the Identification, Characteristics, and Duration of Declines During Economic Slumps - Bluhm, Richard; de Crombrugghe, Denis; Szirmai, Adam (World Bank, Washington, DC, 2020)
This paper studies periods of prolonged contractions in output per capita in a sample of 145 countries from 1950 to 2014. Economic slumps are defined as abrupt interruptions of a period of growth by several regime switches. Slumps start with a sharp contraction along with a trend break, which is followed by another switch when growth stabilizes again. The paper then analyzes the correlates of these slumps, focusing on the length and depth of the contraction, from the beginning of the slump to its trough. The results establish three new stylized facts: (i) weak political institutions predate crises whereas political reforms tend to follow them, (ii) the length and depth of economic declines are robustly correlated with executive constraints and ethnic heterogeneity, and (iii) there is a robust interaction between these two variables, suggesting that institutions constraining leaders are important for stabilizing growth. This is particularly relevant for Sub-Saharan Africa, where politics are often ethnic and decision makers are comparatively unconstrained.